On a class of irreducible polynomials over Fp - Melsik K. Kyuregyan; Edita Yu. Harutyunyan; Mikayel G. Evoyan (Изд-во НАН РА)
The paper presents some results regarding constructive theory of synthesis of irreducible polynomials of degree pt over Fp from the given primitive elements in Fp,where p is an odd prime and t is an integer whose prime factors all divide p -1 .
Keywords: Mathematics